2017
DOI: 10.1186/s41747-017-0025-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast MRI radiomics: comparison of computer- and human-extracted imaging phenotypes

Abstract: BackgroundIn this study, we sought to investigate if computer-extracted magnetic resonance imaging (MRI) phenotypes of breast cancer could replicate human-extracted size and Breast Imaging-Reporting and Data System (BI-RADS) imaging phenotypes using MRI data from The Cancer Genome Atlas (TCGA) project of the National Cancer Institute.MethodsOur retrospective interpretation study involved analysis of Health Insurance Portability and Accountability Act-compliant breast MRI data from The Cancer Imaging Archive, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…This association with breast cancer risk suggests a possible mechanism of correlating underlying biological processes with resultant imaging phenotypes. Deep learning is also being examined for use in assessing breast density and in describing the parenchymal patterns of density on mammograms (Fig. a–c).…”
Section: Risk Assessment and Preventionmentioning
confidence: 99%
“…This association with breast cancer risk suggests a possible mechanism of correlating underlying biological processes with resultant imaging phenotypes. Deep learning is also being examined for use in assessing breast density and in describing the parenchymal patterns of density on mammograms (Fig. a–c).…”
Section: Risk Assessment and Preventionmentioning
confidence: 99%
“…In applications for breast cancer risk assessment, radiomic features have emerged as surrogate measures for breast parenchymal patterns in mammographic and tomographic images . With the expanding use of DCE‐MRI for breast cancer screening, recent studies have suggested associations between radiomic characterizations of BPE and breast cancer risk . Specifically, in each study radiomic features characterizing the morphology, texture, and kinetics of BPE, as well as features quantifying breast density, demonstrated a high correlation with qualitative phenotypic characteristics determined by a radiologist, emphasizing the complementary value of radiomics for breast cancer risk assessment.…”
Section: Radiomic Analysis Of Bpementioning
confidence: 99%
“…Obviously CAD can be considered part of radiomics, but in contrast to CAD's simplicity and ability for answering only simple clinical questions, radiomic analysis considers more complex computational processes aiding decision support, by utilizing a plethora of quantitative imaging features—potential imaging biomarkers, extracted from digital images [ 26 , 28 ]. Furthermore, the correlation of these large-scale radiological phenotypic characteristics with the rich breast histopathological data available, e.g., the expression statuses of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor 2 receptor (HER2), and triple negative (lack of expression of ER, PR, and HER2), facilitates their strong association with molecular subtypes, which eventually results in the generation of pathology prognostic and predictive models [ 4 , 26 , 27 , 29 ].…”
Section: Radiomics and Decision Support In Breast Mrimentioning
confidence: 99%
“…Higher order statistics derived features, referred to as textural features, have been widely utilized in breast tumor DCE-MRI parametric maps in the past, for improving characterization of breast lesions and their response to treatment [ 43 47 ]. Second-order histograms such as gray-level co-occurrence matrices (GLCMs) [ 28 , 48 ] and gray-level run-length matrices (GLRLMs) [ 29 , 49 ] characterize spatial relationships between pixel intensities in different 2D or 3D directions and thus are robust in quantifying tumor structural properties and various patterns of heterogeneity. In particular, GLCM analysis of DCE MR data has been proved to be robust in differentiating between benign and malignant breast lesions [ 50 ].…”
Section: Radiomics Analysis Workflowmentioning
confidence: 99%